2022
DOI: 10.2176/jns-nmc.2022-0116
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Revolution of Imaging Technologies in Neurosurgery

Abstract: We understand only a small fraction of the events happening in our brains; therefore, despite all the progress made thus far, a whole array of questions remains. Nonetheless, neurosurgeons invented new tools to circumvent the challenges that had plagued their predecessors. With the manufacturing boom of the 20th century, technological innovations blossomed enabling the neuroscientific community to study and operate upon the living brain in finer detail and with greater precision while avoiding harm to the nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Additionally, the 3D model can easily be converted into AR, mixed reality (MR), and virtual reality (VR) forms, providing even more detailed and interactive visuals for medical professionals [1,6]. These advanced technologies can result in reduced complications and shorter hospital stays for patients, ultimately leading to better outcomes overall [15]. Sato et al [17] demonstrated that 3D-MFI is more effective than conventional 2D images for learning skull base meningioma surgery, providing accurate identi cation of anatomical structures and promising educational and surgical planning bene ts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the 3D model can easily be converted into AR, mixed reality (MR), and virtual reality (VR) forms, providing even more detailed and interactive visuals for medical professionals [1,6]. These advanced technologies can result in reduced complications and shorter hospital stays for patients, ultimately leading to better outcomes overall [15]. Sato et al [17] demonstrated that 3D-MFI is more effective than conventional 2D images for learning skull base meningioma surgery, providing accurate identi cation of anatomical structures and promising educational and surgical planning bene ts.…”
Section: Discussionmentioning
confidence: 99%